vp100811_elic_VerbalForms_Vstatj - Валентина Пуяковна Силкина (Надер); Андрей Шлуинский (Bernard Comrie, 2010)
А.Шлуинский собирает с В.П.Надер модально-временные формы глагола nOOrO- 'встать' A.Shluinsky collects with V.P.Nader TAM forms of the verb nOOrO- 'stand up' Language_Name: Enets Language_Region: Asia Language_Country: Russia Project_Status: Complete Year: 2007 Start_Date: 2008-02-01 End_Date: 2011-01-31 Title vp100811_elic_VerbalForms_Vstatj